VALUES OF MOLDOVANS HIGH SCHOOL STUDENTS FROM ITALY AND THE REPUBLIC OF MOLDOVA: A CROSS-CULTURAL ASPECT - CAUNENCO Irina; ROȘCA Tatiana (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The article analyzes the features of the value sphere in high school students - children of Moldovan migrants from Italy and in high school students from the Republic of Moldova. Thus, the axiological meanings are evaluated, they revealed both common values and distinct values. Therefore, if for schoolchildren - sons of Moldovan migrants, the priority values are: interesting work and material security, then for their colleagues from the Republic of Moldova, the priority belongs to the spheres of life: family and health. At the same time, we want to mention the fact that for both groups, aesthetic values had little importance. Thus, against the background of the obtained results, there is a need to take more into account the particularities of the value sphere, especially in the case of migrant children from the diaspora.